Reading-Related Skills Associated With Acquisition of Chinese as a Second/Foreign Language: A Meta-Analysis - Chen, Xi; Zhao, Jingjing (Frontiers in Psychology, 2022)
Previous studies have found the effect of cognitive skills (e.g., phonological awareness, morphological awareness, orthographic awareness, and rapid automatized naming) on reading ability, but the role of different reading-related skills in acquisition of Chinese as a second/foreign language (CSL/CFL) remains unexplored. Prior meta-analyses on the relationship between cognitive skills and reading have been conducted primarily in native English-speaking or Mandarin-speaking children. The purpose of the present meta-analysis was to examine the relationship between Chinese reading-related skills and Chinese word reading of CSL/CFL learners. A search of English and Chinese databases yielded 42 effect sizes, comprising 1103 subjects met the criteria for meta-analysis and were included in the final meta-analysis. Results revealed a moderate relationship between phonological awareness (r = 0.41), morphological awareness (r = 0.36), orthographic awareness (r = 0.38), rapid automatized naming (r = −0.32) and Chinese word reading in CSL/CFL learners. In addition, a moderating effect of length of study on the relationship between phonological awareness and Chinese word reading (QB = 5.20, p = 0.023): phonological awareness and Chinese word reading correlated more strongly for beginning learners than for advanced learners. These results suggest importance of cognitive factors in the acquisition of Chinese word reading as a second language. Results also shed light on the impact of length of study on the influence from phonological awareness to the sensitive period of phonological learning for CSL/CFL learners.